Organic matter–mineral associations in organic horizons in high-altitude areas of snowy mountains, northern Japan - Koya Kobayashi; Maki Asano; Ryoji Tanaka; Silver Sung-Yun Hsiao; Shan-Li Wang; Kenji Tamura; Der-Chuen Lee (CATENA, 2026)

Involvement of FoxO1, Sp1, and Nrf2 in Upregulation of Negative Regulator of ROS by 15d-PGJ2 Attenuates H2O2-Induced IL-6 Expression in Rat Brain Astrocytes - Chen-Yu Wang; Chien-Chung Yang; Li-Der Hsiao; Chuen-Mao Yang (Neurotoxicity Research, 2022)
Excessive production of reactive oxygen species (ROS) by NADPH oxidase (Nox) resulted in inflammation. The negative regulator of ROS (NRROS) dampens ROS generation during inflammatory responses. 15-Deoxy-∆12,14-prostaglandin J 2 (15d-PGJ 2 ) exhibits neuroprotective effects on central nervous system (CNS). However, whether 15d-PGJ 2 -induced NRROS expression was unknown in rat brain astrocytes (RBA-1). NRROS expression was determined by Western blot, RT/real-time PCR, and promoter activity assays. The signaling components were investigated using pharmacological inhibitors or specific siRNAs. The interaction between transcription factors and the NRROS promoter was investigated by chromatin immunoprecipitation assay. Upregulation of NRROS on the hydrogen peroxide (H 2 O 2 )-mediated ROS generation and interleukin 6 (IL-6) secretion was measured. 15d-PGJ 2 -induced NRROS expression was mediated through PI3K/Akt-dependent activation of Sp1 and FoxO1 and established the essential promoter regions. We demonstrated that 15d-PGJ 2 activated PI3K/Akt and following by cooperation between phosphorylated nuclear FoxO1 and Sp1 to initiate the NRROS transcription. In addition, Nrf2 played a key role in NRROS expression induced by 15d-PGJ 2 which was mediated through its phosphorylation. Finally, the NRROS stable clones attenuated the H 2 O 2 -induced ROS generation and expression of IL-6 through suppressing the Nox-2 activity. These results suggested that 15d-PGJ 2 -induced NRROS expression is mediated through a PI3K/Akt-dependent FoxO1 and Sp1 phosphorylation, and Nrf2 cascade, which suppresses ROS generation through attenuating the p47 phox phosphorylation and gp91 phox formation and IL-6 expression in RBA-1 cells. These results confirmed the mechanisms underlying 15d-PGJ 2 -induced NRROS expression which might be a potential strategy for prevention and management of brain inflammatory and neurodegenerative diseases.

Arachidonic Acid Induces ARE/Nrf2-Dependent Heme Oxygenase-1 Transcription in Rat Brain Astrocytes - Chih-Chung Lin; Chien-Chung Yang; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2018)

Thrombin Enhanced Matrix Metalloproteinase-9 Expression and Migration of SK-N-SH Cells via PAR-1, c-Src, PYK2, EGFR, Erk1/2 and AP-1 - Chien-Chung Yang; Li-Der Hsiao; Chuen-Mao Yang; Chih-Chung Lin (Molecular Neurobiology, 2017)

Thrombin/Matrix Metalloproteinase-9-Dependent SK-N-SH Cell Migration is Mediated Through a PLC/PKC/MAPKs/NF-κB Cascade - Chien-Chung Yang; Chih-Chung Lin; Peter Tzu-Yu Chien; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

CO Induces Nrf2-Dependent Heme Oxygenase-1 Transcription by Cooperating with Sp1 and c-Jun in Rat Brain Astrocytes - Pei-Ling Chi; Chih-Chung Lin; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

BK Induces cPLA2 Expression via an Autocrine Loop Involving COX-2-Derived PGE2 in Rat Brain Astrocytes - Chih-Chung Lin; Hsi-Lung Hsieh; Shiau-Wen Liu; Hui-Ching Tseng; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Upregulation of COX-2/PGE2 by ET-1 Mediated Through Ca2+-Dependent Signals in Mouse Brain Microvascular Endothelial Cells - Chih-Chung Lin; Hsi-Lung Hsieh; Pei-Ling Chi; Chien-Chung Yang; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Erratum to: High Glucose Induces Reactive Oxygen Species-Dependent Matrix Metalloproteinase-9 Expression and Cell Migration in Brain Astrocytes - His-Lung Hsieh; Chih-Chung Lin; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2013)

Thrombin Mediates Migration of Rat Brain Astrocytes via PLC, Ca2+, CaMKII, PKCα, and AP-1-Dependent Matrix Metalloproteinase-9 Expression - Chih-Chung Lin; I-Ta Lee; Wen-Bin Wu; Chiung-Ju Liu; Hsi-Lung Hsieh; Li-Der Hsiao; Chien-Chung Yang; Chuen-Mao Yang (Molecular Neurobiology, 2013)

High Glucose Induces Reactive Oxygen Species-Dependent Matrix Metalloproteinase-9 Expression and Cell Migration in Brain Astrocytes - Hsi-Lung Hsieh; Chih-Chung Lin; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)